2015
DOI: 10.1007/s10067-015-3121-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties of low-dose SoluMatrix meloxicam in healthy adults

Abstract: SoluMatrix® meloxicam has been developed using SoluMatrix Fine Particle Technology™ to produce a meloxicam drug product with enhanced absorption properties to enable treatment at lower doses than available oral meloxicam drug products. This follows recognition of serious dose-dependent adverse events (AEs) associated with nonsteroidal anti-inflammatory drugs, including meloxicam. This study investigated the pharmacokinetic (PK) properties of SoluMatrix meloxicam 5-mg (fasting conditions) and 10-mg capsules (fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The manufacturing process, which does not alter the active therapeutic ingredient, was previously shown to promote rapid absorption of new formulations of diclofenac and meloxicam [11, 12]. The present study in healthy subjects indicates that the use of SoluMatrix Fine Particle Technology™ enhances the bioavailability of abiraterone acetate.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The manufacturing process, which does not alter the active therapeutic ingredient, was previously shown to promote rapid absorption of new formulations of diclofenac and meloxicam [11, 12]. The present study in healthy subjects indicates that the use of SoluMatrix Fine Particle Technology™ enhances the bioavailability of abiraterone acetate.…”
Section: Discussionmentioning
confidence: 51%
“…Reduced particle size leads to an enhanced surface area, and this in turn leads to an enhanced rate of dissolution and absorption [11, 12]. The absorption of OAA is reported to be nearly saturated at a dose of 1000 mg [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, nanotechnologies for OA are still under development, with very few clinical experiments. A search in the PubMed database and the Clinicaltrials register highlighted that NPs are generally tested as nano-based emulsions or formulations to deliver analgesic NSAIDs or anti-inflammatory gold nanoparticles by topical and oral applications, and these clinical studies, mostly of phases one and two, demonstrated safety and efficacy with significantly improved pain, stiffness, and physical function in patients affected by OA [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] (NCT00484120, NCT05347602).…”
Section: Discussionmentioning
confidence: 99%
“…Meloxicam is an oxicam, which has a low COX-2/ COX-1 ratio, with the inhibitory effect more focused on the inflammatory proteins (COX-2) with relatively little effect on the homoeostatic proteins (COX-1). Meloxicam is a frequently prescribed nonsteroidal antiinflammatory drug (NSAID) in the USA and is prescribed for the treatment of osteoarthritis (OA), rheumatoid arthritis (RA) and juvenile RA [3,4] . It is also one of the few NSAIDs approved for use in animals [4] .…”
mentioning
confidence: 99%
“…In the dissolution process of sparingly soluble substances, an important role among auxiliary substances is played by surfactants [8,9] . The presence of surfactants in suppositories for rectal administration can cause some changes in the properties of the suppository base [3,10] . In particular, adding a surfactant to suppositories can facilitate the spread of the suppository bases in the rectum.…”
mentioning
confidence: 99%